Association between interpregnancy interval and adverse perinatal outcomes according to maternal age in the context of China’s two-child policy - SiQin Xiu; Li Tang; Chengjie Qin; Di Tian; Yuhong Chen; Lingling Gu; Liu Yang; Yuhao Sun; Xinghui Liu; Yonghong Lin; Yumei Wang (BMC Pregnancy and Childbirth)
Abstract Background Since the implementation of China’s comprehensive two-child policy, the prevalence of long interpregnancy intervals (IPI) and advanced maternal age has increased. However, previous studies in China have mostly focused on the relationship between short IPIs and adverse perinatal outcomes, while neglecting maternal age as a potential confounder. Methods We conducted a retrospective cohort study of 23,899 pregnant women who delivered between January 1, 2017 and December 31, 2019 at Chengdu Women’s and Children’s Central Hospital and West China Second Hospital of Sichuan University. IPIs were categorized as < 18 months, 18–23 months, 24–59 months, 60–119 months, and ≥ 120 months. Their relationships with clinical characteristics and pregnancy outcomes were analyzed using chi-square tests and Cochran-Armitage test for trend. Logistic regression modeling, incorporating restricted cubic spline (RCS), was used to assess association between IPI and adverse perinatal outcomes, including full-term low birthweight (LBW), preterm birth (PTB), small-for-gestational age (SGA) and adverse neonatal composite (very low birthweight, very preterm birth, severe neonatal asphyxia or death). Results Women with longer IPIs (≥ 120 months) were more likely to be older (≥ 35 years) and had higher rates of gestational diabetes and hypertensive disorders of pregnancy (p < 0.05). Compared to an IPI of 24–59 months, the risk of PTB was significantly higher with an IPI of ≥ 120 months for women aged ≥ 35 years (aOR,1.17; 95% CI, 0.89–1.55) and 30–34 years (aOR 2.17; 95% CI, 1.59–2.92), but not for those aged ≤ 29 years (aOR 1.34; 95% CI, 0.20–5.31). The risk of SGA increased with an IPI of ≥ 120 months for women aged 30–34 years (aOR, 2.19; 95% CI, 0.97–4.53) and with an IPI of 60–119 months for women aged ≤ 29 years (aOR,3.16; 95% CI, 1.62–6.30). Full-term LBW risk was elevated among women aged ≤ 29 years with an IPI of ≥ 120 months (aOR, 10.42; 95% CI, 0.55–59.52). However, there were no significant differences in the risk of adverse neonatal composite across different IPI groups with each age category (p > 0.05). Conclusion A long IPI increased the risk of SGA, full-term LBW and PTB, regardless of maternal age. Medical professionals should advise women an optimal IPI to mitigate these risks. With China’s shift from a “one-child” to a “three-child” policy, future research will focus on analyzing this new fertility pattern to refine IPI recommendations.